(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Identification of the features of the course of gestation, childbirth and the postpartum period in pregnant women of reproductive age is one of the urgent problems of practical medicine. The results of hormonal and them ¬ munological studies conducted by the - Smooth puerperal with preserved lacquer function ¬ tations are important in studying the processes of formation of their reproductive function. Thus, the data obtained ¬ This results in the absence of normalization of FSH, LH, progesterone and estradiol levels in the first 2 weeks of the postpartum period.